Between extractivism and peasant agriculture: differentiation of rural settlements in the Bolivian Amazon - Stoian, D.; Henkemans, A. (2000)
The economy of the northern Bolivian Amazon has historically been based on rubber and other non-timber forest products (NTFPs). In the late 19th century, the upcoming rubber boom lead to the establishment of rubber estates. Following World War I, a first rubber crisis forced some estate owners to abandon their land, favouring the emergence of independent communities. A second rubber crisis after World War II, along with the Agrarian Reform in 1953, accelerated the disintegration of rubber estates and the foundation of independent communities. In the early 1990s, the conclusive halt of Bolivian rubber production fuelled rural-urban migration and the differentiation of rural settlements. This paper examines the evolution from pure rubber estates to a wide array of settlement types. A settlement typology distinguishes four types of estates and six types of independent communities with varying trade-offs between extractivism and peasant agriculture. The findings have important implications for NFTP-based development. First, extraction-based livelihoods are socially acceptable only when access to basic services, such as schooling, health care, and transportation, is ensured. Second, in the region's remote areas the supply of such services needs to rely on a forest concession system within which the private sector bears the required investments. Finally, indigenous communities participating in NTFP trade need to demarcate their sphere in between the remote forest concessions and the non-tribal peasantry in the vicinity of town.